0; -6; 6
Пошаговое объяснение:
||х| - 3| = 3
1)
|х| - 3 = -3
|х| = -3 + 3
|х| = 0
х1 = 0
2)
|х| - 3 = 3
|х| = 3 + 3
|х| = 6
х2 = -6
х3 = 6
1) x-4 1/2= -2 1/4
x= -2 1/4+4 1/2 =-9/4+9/2=(-9+19)/4=9/4
x=9/4
2) -x-6 4/5=3 1/2
-x=3 1/2+6 4/5 = 7/2+34/5=(35+68)/10=103/10=10 3/10
-x=10 3/10
x= -10 3/10
3) -x-11 1/2= -4 7/8
-x= -4 7/8+11 1/2 = -39/8+23/2=(-39+92)/8=53/8=6 5/8
-x=6 5/8
x= -6 5/8
ответ: x∈{-6;0;6}
Пошаговое объяснение:
IIxI-3I=3 => IxI=6 либо IxI =0
Если IxI=6 , то х =-6 либо х=6
Если IxI=0 , то х =0
ответ x∈{-6;0;6}